Safety population size and duration of exposure prior to approval of new medicines: A database analysis of medicines centralised approved in the European Union between 2011 and 2023 - Luísa Bouwman; Hubert Leufkens; Bruno Sepodes; Carla Torre (PLoS ONE, 2026)
Background This study aims to analyse the number of patients who had been exposed to a new medicine before the approval by the European Commission (EC), as well as the number of patients studied long-term for chronic medication use. The results were compared with the International Council for Harmonisation’s (ICH) E1 guideline recommendations. Methods All medicines containing new active substances approved between 2011 and 2023 were included in the study, including orphan medicines as a separate category. The total number of patients studied and the number of patients with long-term use (6 and 12 months) for chronic medication before approval were extracted. In addition, information regarding the type of Marketing Authorisation (MA), type of molecule, Anatomical Therapeutic Chemical (ATC) code and additional pharmacovigilance activities were extracted from the European Public Assessment Report (EPAR). Results A total of 498 new medicines were identified, of those 322 were non-orphan medicines and 176 were orphan medicines. The median total number of patients studied before approval was 1,787 (interquartile range [IQR] 781–3,351) for non-orphan medicines and 333 (IQR 139–648) for orphan medicines. In the group of non-orphans, chronic medication was studied in a larger number of patients (median 2,253, IQR 1,523–3,662) than medication for intermediate (median 798, IQR 520–1,757) or short-term use (median 2,038, IQR 807–6,110). Among the 154 non-orphan medicines intended for chronic use, 83 (54%) met the patient exposure recommendations for 6-months use, and 113 (73%) met the criteria for 12-months patient exposure. Among the 101 orphan medicines intended for chronic use, only 1 (1%) met the patient exposure recommendations for 6-months use and 7 (6.9%) met the criteria for 12-months patient exposure. Conclusion Orphan medicines and “precision” medicines tend to have less clinical data available at the time of marketing authorisation. The median of the total number of subjects studied prior to approval has been decreasing overtime. Additional pharmacovigilance activities play, in these cases, a key role in the safety monitoring and assessment of the benefit-risk profile during the medicine’s lifecycle.